Busca de novos compostos orgânicos naturais com potencial esquistossomicida - Pereira, Aline (2013)
Schistosomiasis is a neglected tropical disease with high morbidity and mortality, which currently affects over 200 million people around the world. For the World Health Organization praziquantel (PZQ) is the drug of choice for treatment of infected individuals, because it has a broad spectrum of activity against S. mansoni. However, few studies describe several strains of the parasite that are resistant to PZQ, making studies of new drugs that can be used in the treatment of schistosomiasis necessary. In this sense, the properties of the schistosomicidal ethanolic extract of Garcinia brasiliensis epicarp and its fractions obtained by partitioning, such as hexane, the ethyl acetate, the aqueous and the compounds isolated and 7-epiclusianone and fukugetina were tested in vitro with adult worms of Schistosoma mansoni. The results indicate that the hexane fraction showed better activity in vitro on adult worms of S. mansoni, when compared with the ethanol extract of the G. brasiliensis epicarp and with ethyl acetate and aqueous fractions. Based on this finding a chromatogram was made and the results confirmed the 7-epiclusianone as major component of the hexane fraction. This fraction was then chromatographed on silica gel column providing the purified molecule 7-epiclusianone, which showed significant activity against schistosomula, cercariae and adult worms of S. mansoni. Activity on adult worms was investigated by monitoring the mortality, surface membrane damage and excretory system activity, where the damage to the surface of the membrane and on the activity of the excretory system could be observed by fluorescent probes Hoechst 33258 and Resorufin, respectively. The results indicate its strong effect against all stages of parasite and also showed an inhibitory effect on the oviposition of female adult worms of S. mansoni when compared with the original extract and its fractions. Synergistic activity of 7-epiclusianone was also evaluated in vitro in combination with Praziquantel, and synergistic effects were observed due to this association. The efficacy of 7-epiclusianone alone and in combination with PZQ in vivo has been evaluated through counting and distribution of worms in the liver and the mesentery and changes in oogram. In the chemotherapy regimen used, the 7-epiclusianone showed no schistosomicidal activity and the result of the combination with praziquantel was not significantly different from that obtained when these latter two drugs were administered alone. The in vitro results obtained in the present study confirm that the ethanol extract of the G. brasiliensis epicarp and its fractions hexane, ethyl acetate and the isolated substance 7-epiclusianone alone and in combination with PZQ shows strong schistosomicidal activity. However, in preliminary tests in vivo it was not possible to observe the 7-epiclusianone alone and in combination with praziquantel effects found in in vitro tests. Probably this is related to the fact that 7-epiclusianone be a highly liposoluble substance which makes its solubility difficult in appropriate solvents for oral administration. Subsequent tests will be conducted in order to study the change of the 7-epiclusionone lipophilicity in vitro and in vivo schistosomicidal assays.